Empathy, Emotions and Patient-centredness: a Case Study on Communication Strategies - Muñoz-Miquel, Ana (HERMES - Journal of Language and Communication in Business, 2019)
One of the abilities most often associated with patient-centred communication (PCC) is empathy. But how can it be achieved? There is an extensive literature acknowledging the importance of communication skills in healthcare settings. However, few studies focus on the specific strategies that can help overcome the challenges posed by PCC, especially in dealing with, understanding and responding to emotions. This is especially evident in the field of written communication. Starting from the assumption that the way in which medical information is conveyed can significantly influence receivers’ emotional response, and thus their understanding, this paper explores oral and written communication strategies that might be useful for fostering empathy. These strategies are based on the results of two funded research projects carried out by the Gentt Group (Universitat Jaume I, Spain), in which qualitative methods (interviews, focus groups and role-play with real actors) were used to improve doctor-patient communication in intralingual and interlingual contexts, in two genres: fact sheets for patients and medical consultations. The results show that avoiding ambiguous and alarming words, providing explicit explanations, using ‘you’ or the inclusive plural when addressing the patient, framing statements in a positive way, and explaining medical terms can all help enhance empathy, both in oral and written modes. In oral genres, non-verbal communication can also play a key role in showing genuine understanding. The importance of obtaining feedback from real patients and the potential of intralingual translation and role-play for improving the communication skills of medical professionals, translators and interpreters are also discussed.